2013
DOI: 10.1080/09537325.2012.759200
|View full text |Cite
|
Sign up to set email alerts
|

Public R&D funding: does the source determine the strategy?

Abstract: Abstract:The aim of this study is to analyze whether the receipt of public funding for innovation determines for present and future a firm's choice of R&D strategy. We consider three R&D strategies: make R&D in-house, buy R&D and, combined make-buy R&D. The analysis uses a sample of 457 large firms for the period 1992-2005, taken from the Spanish Survey of Business Strategies. Estimation of a multinomial logit model with random effects shows that the positive effect of public funding varies according to the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…This in line with Ebersberger et al (2011) who observed that public funding fosters higher levels of collaboration in technology-user countries than in technology-leader countries. Further, our results extend Bayona-Sáez et al ’s (2013) arguments that public funding exerts an influence on the innovation strategy and that its effects are not equal in all regions. Therefore, although government funding for R&D activities incentivises to look for external sources of information to innovate and to establish formal cooperation agreement, policymakers should pay special attention to the specific contextual conditions when developing public policies to encourage inbound OI practices.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This in line with Ebersberger et al (2011) who observed that public funding fosters higher levels of collaboration in technology-user countries than in technology-leader countries. Further, our results extend Bayona-Sáez et al ’s (2013) arguments that public funding exerts an influence on the innovation strategy and that its effects are not equal in all regions. Therefore, although government funding for R&D activities incentivises to look for external sources of information to innovate and to establish formal cooperation agreement, policymakers should pay special attention to the specific contextual conditions when developing public policies to encourage inbound OI practices.…”
Section: Discussionsupporting
confidence: 82%
“…For example, some surveyed firms participating in public programmes strengthened their networks and collaboration with other firms (Georghiou and Clarysse, 2006). Some researches (Ebersberger et al , 2011; Bayona-Sáez et al , 2013) found that public funding for R&D is not only a factor influencing firms’ decisions to undertake R&D activities, but also a factor that determines firms’ choice of R&D strategy.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of intramural R&D as an engine of innovations is unquestionable [28,35], since it enables more fluid communication between the different departments involved, creates firm-specific knowledge and generates absorptive capacity, which favors greater economies of scale and minimizes transaction costs [36][37][38]. However, these beneficial effects can be counterbalanced by less predictable and riskier outcomes, as well as by a higher probability of remaining isolated in a particular technological development [39,40].…”
Section: Innovation Inputsmentioning
confidence: 99%
“…Both measures of innovation inputs are three year lagged [32,88] due to the purpose of this study and because of the nature of the dependent variable, which is calculated using lagged averaged performance data during the past three years. These lags aim to determine whether R&D investments have a temporary effect on sustainable economic performance [39]. In this regard, it is widely acknowledged that both intramural and extramural R&D strategies usually constitute long-term processes whose performance outcomes are obtained in later years after their implementation [28].…”
Section: Independent Variablesmentioning
confidence: 99%